Deepfakes, dificultades probatorias y su incidencia en la vulneración al derecho de intimidad - Sinaluisa Sagñay, Franklin Geovanny (2024)
ABSTRACT: The "deepfakes" are fake videos or images created with artificial intelligence that incurs a violation of privacy and intimacy. This act arose in 2017 specifically to make fake sex videos without the consent of the person. The right to privacy is a fundamental right that protects the private life of each individual. The present research project deals with the lack of typification in Ecuador on "deepfakes" and its relationship with the evidentiary difficulties that this entails. It was carried out using a qualitative, documentary, bibliographic, dogmatic, descriptive, and descriptive research method, which contains a non-experimental design. It is worrying that "deepfakes" invade privacy and intimacy using data found in social networks or on any website (big data) Comparative law helps to study legislation to give perspectives on reform that can solve this problem effectively and determine its applicability in possible future cases in Ecuador. The lack of criminalization of this act directly affects the right to privacy of individuals in future cases, so it lighlights the need to implement the Organic Criminal Code, regulations to prevent and punish these malicious digital manipulations, also implement the tools and methods of investigation to find the origin and the responsible for the creation of the "deepfake," as well as pointing out the lack of experts specialized in Artificial Intelligence. A real case is analyzed, and different legislations are examined to understand the current legal challenges and propose reliable legal solutions. Keywords: Pornograpluc deepfake, female victims, privacy rights, artificial intelligence, privacy